Analysis on detection of trend in groundwater level in mid-western plain zone, India - GANGWAR, ANSHU; SINGH, SURJEET; SINGH, R.M.; SHARMA, GAURAV; TIRKEY, NITY; SINGH, GAURAV; VERMA, RAMESH; GUNJAN, PRIYANKA (Journal of Soil and Water Conservation, 2023)
The inefficient approach to water utilization resulted in unforeseen consequences like water scarcity which resulted from human-induced activities. Excessive groundwater utilization has caused an imbalance in the natural groundwater flow regime (GWFR). The variability in the GWFR causes deprivation of natural flows in rivers and affects the environment and society by and large. Evaluation of groundwater level trends during the pre and post-monsoon is utterly required which will help in rendering its ill effects. In this context, a study has been carried out to investigate the trend in groundwater level for two districts (Bareilly and Pilibhit) under mid-western plain zone of Uttar Pradesh, India using statistical parameters, Mann-Kendell (MK) test, Sen Slope Estimator (SSE) test and Inverse Distance Weighting (IDW) method of interpolation for spatial distribution of groundwater level. Statistical analysis showed that the variability in groundwater level was significantly higher during the PTM than the PRM periods. MK test results indicated that there is a significant rising trend in groundwater levels in 10 blocks during pre-monsoon period and 11 blocks during the post-monsoon period. The magnitude of change as evaluated using Sen’s slope method suggested that all blocks are showing declining groundwater level in the region except Puranpur block (-0.036 m/yr) and Marauri Block (-0.015 m/yr) which represents adequate groundwater. This declination of groundwater level may affect farming community of this region. Hence, this analysis will help the stakeholders to focus on management techniques to ensure groundwater resource management in a sustainable way.